Electron Field Emission from Water-Based Carbon Nanotube Inks. (1st January 2015) - Lyth, S. M.; Silva, S. R. P.
Abstract : Printable electron field emitters could lead to cheap and scalable large area electron sources. This paper presents work on electron field emission from water-based multiwall carbon nanotube (MWCNT) dispersions, and introduces new results on emission from different substrates. We summarize work in which MWCNTs are deposited onto paper, glass, and plastic substrates, and show that the field emission characteristics can be tailored by controlling the underlying morphology as well as by post-laser irradiation. We also show that engineering the work function of MWCNTs can significantly enhance field emission, and that resonant tunneling effects may be induced by suitable surface functionalization.